DEVELOPMENT OF A MODEL TO INCREASE TECHNOLOGY USE FOR MUSIC INSTRUCTORS IN SICHUAN PROVINCE, CHINA - Huang, Yawen; Asavisanu, Poonpilas (Journal of Buddhist Education and Research (JBER), 2024)
The use of technology for music instruction is an essential aspect of the development of creative and innovative music professionals. Nevertheless, the use of technology for music teaching in China is still developing in many areas. This study intended to develop a model to increase technology use by music instructors in Sichuan province. It utilized a sequential exploratory mixed methods design to develop a model and was based on two theories, TPACK and UTAUT. The study was based on the following objectives: 1)To explore the type of technological, content, and pedagogical knowledge of university music instructors and their intention to use technology 2) To determine the current levels of technological, pedagogical, and content knowledge and the intent to use technology of music instructors in universities in Sichuan province, 3) To find the relationship between university music instructors' content, pedagogical, and technological knowledge, and their intention to use technology 4) To develop a model to increase technology use for music instructors in Sichuan Province, China. Respondents were 412 music instructors from four universities in Sichuan province. Perceived pedagogical and content knowledge levels were high and technological knowledge was moderate. Instructors’ intent to use technology was also high. Regression analysis revealed that there was a statistically significant relationship between instructors’ levels of technological, content, and pedagogical knowledge and intent to use technology. The multiple regression results indicated that as R2 = .45, where TPACK accounted for 45.5% of the variance related to intent to use technology. A final model was developed and validated by experts.